Students and academicians views on the engineering curriculum and industrial skills requirement for a successful job career - Gope Deepayan; Gope Aditya (De Gruyter, 2022)
Due to rapid advancement of technology, engineers should have a set of engineering skills. The basic knowledge about engineering skills should be imparted during graduation. In this study, an attempt is made to assess the gap between the present course curriculum that engineering institutions are exposing their engineering students and the skills required by the industries. Views of engineering students and academicians are obtained through questionnaires and analyzed using statistical tools. The results revealed that strong analytical ability, able to adapt and learn new technology, problem-solving within stipulated period or deadlines, and work promotion are the most important factors for a successful future job performance. The study also reveals that a significant gap exists between learning skills like communication, systematic work plan, and furtherance of work done. It is also seen that the use of modern tools and knowledge up-gradation is important to acquire many required industrial skills for a successful job career and the present curriculum is not effective to impart training on these aspects.